Factors affecting the realisation of child-bearing intentions in four European countries - Balaźs Kapitańy; Zsolt Sped́er (Hungarian Demographic Research Institute, 2011)
This study investigates the realisation of time-related positive fertility intentions using a comparative approach. Four European countries of medium size are compared, all with rather different fertility regimes: the Netherlands and Switzerland (Western), and Hungary and Bulgaria (Post-communist). Using four harmonised longitudinal panel surveys, it is possible to construct a typology of fertility intentions and outcomes, and not only to identify common patterns but also different influencing factors in each country. By employing multinominal logistic regressions, we uncover factors influencing postponement, abandonment and realisation of childbearing. In all four countries, age, partnership status and education appear to influence fertility intentions in the same ways. However, the effects of some of these factors do differ in the four countries that we focus on.
Keywords: J13; 300; fertility; fertility intention; childbearing intention; fertility behaviour; fertility dynamics; postponement; Europe; comparison; panel survey; Bevölkerung; Geschichte; Demographie; Ungarn